Facile and Efficient Patterning Method for Silver Nanowires and Its Application to Stretchable Electroluminescent Displays - Lin, Yong; Yuan, Wei; Ding, Chen; Chen, Shulin; Su, Wenming; Hu, Hailong; Cui, Zheng; Li, Fushan (ACS applied materials & interfaces, 2020)
The patterning of silver nanowires (AgNWs) is subject to critical challenges, which have seriously limited their practical applications. This work describes a simple and efficient method combining screen printing with vacuum filtration for patterning AgNW networks. The screen-printed poly(dimethylsiloxane) (PDMS) mask layer was shown to be strongly adhered to the filtration membrane, which resulted in well-defined sharp edges of the deposited AgNW patterns, and a 50 μm patterning resolution was achieved. The patterned films with low densities of AgNWs (≤15 μg/cm ) were transferred to the surface of PDMS to make patterned stretchable transparent conductive films (TCFs). The low sheet resistance of 7.3 Ω/sq was achieved at an optical transmittance of 79.6% (at 550 nm wavelength) with a AgNW deposition density of only 12.5 μg/cm . As an application example, the patterned TCFs were used as the top electrodes to fabricate stretchable alternating current electroluminescent (ACEL) displays with stretchability up to 70% of their original dimension, which were applied to a smart system for simulating heart beats together with a digitally operated flexible circuit. The ACEL device exhibited a bright and uniform emission with a clear and smooth edge even with a pattern width as narrow as 100 μm, as well as exceptional elasticity and durability in spite of bending, stretching, and twisting. The present work provides a new way of patterning AgNWs and can be extended to a variety of applications.